2016
DOI: 10.1371/journal.pone.0159438
|View full text |Cite|
|
Sign up to set email alerts
|

To Check or Not to Check? A Qualitative Study on How the Public Decides on Health Checks for Cardiovascular Disease Prevention

Abstract: BackgroundMore than half of the general population does not attend screening for cardiovascular diseases (CVD) hence they are unaware of their risks. The objective of this study was to explore the views and experiences of the public in deciding to undergo health checks for CVD prevention.MethodsThis was a qualitative study utilising the constructivist grounded theory approach. A total of 31 individuals aged 30 years and above from the community were sampled purposively. Eight interviews and six focus groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…However, a systematic review examining customer attitudes found that they were more receptive to the availability of medi-cine-related services than health promotion or screening services, but those who experienced these pharmacy services were highly satisfied with them (12). In a recent Australian atrial fibrillation screening study, pharmacists perceived combining screening with other established services, such as medication reviews, as an alternative approach to improve service uptake (29). Similarly, in this qualitative study, pharmacists observed an improvement in the customers' response to the CKD service when it was integrated with other professional services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a systematic review examining customer attitudes found that they were more receptive to the availability of medi-cine-related services than health promotion or screening services, but those who experienced these pharmacy services were highly satisfied with them (12). In a recent Australian atrial fibrillation screening study, pharmacists perceived combining screening with other established services, such as medication reviews, as an alternative approach to improve service uptake (29). Similarly, in this qualitative study, pharmacists observed an improvement in the customers' response to the CKD service when it was integrated with other professional services.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that, to improve customer awareness and participation in pharmacy services, pharmacists need to reassess their daily practice and ensure that they are not just dispensing prescriptions (27,29). Instead, pharmacists should play an active role by directly approaching customers and explaining available services, and by using prominent flyers (29). Similarly, pharmacists in this study found investing more time in explaining the service to customers, and the use of additional flyers or newsletters, improved the service implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…As such, nonattendees tended to think 'it may happen to others, but not to me', despite being aware of increased risk due to cardiovascular risk factors (20,21). According to Cheong et al (22), patients' motivation for accepting screening is related to their preparedness to deal with the test results, including a diagnosis and need for interventions (both medical and lifestyle modi cations). In addition, Dahl et al (21) found that nonattendance was related to preferring unclarity and wanting not to disturb the feeling of being healthy or running the risk of discovering health problems.…”
Section: Introductionmentioning
confidence: 99%
“…To improve participation rates of health checks for prevention of CVD, it is crucial to understand factors that influence individuals’ intention to go for such checks. We addressed this by first exploring factors that influenced individuals’ decision-making to undergo health checks for CVD prevention in a previous qualitative study [ 7 ]. Following this, a questionnaire was developed to identify the factors that influenced individuals’ intention to undergo health checks for CVD prevention using a quantitative study on a population.…”
Section: Introductionmentioning
confidence: 99%
“…A number of questionnaires have been used in previous studies to examine factors influencing individuals’ intention to participate in health checks using the health belief model [ 9 – 12 ] or the theory of planned behaviour [ 13 , 14 ]. However, the items used were not grounded to local context and the concepts measured did not include all determinants found in our qualitative study [ 7 ]. Thus, we aimed to develop and validate a questionnaire that assessed all determinants that could influence individuals’ intention to undergo CVD health-checks.…”
Section: Introductionmentioning
confidence: 99%